Valuing Diversity - Fryer, Roland G.; Loury, Glenn C. (Journal of Political Economy, 2013)
This paper explores the economics of diversity-enhancing policies. A model is proposed in which heterogeneous agents, distinguished by skill level and social identity, purchase productive opportunities in a competitive market. We analyze policies designed to raise the status of a disadvantaged identity group. When agent identity is contractible, efficient policy grants preferred access to slots but offers no direct assistance for acquiring skills. When identity is not contractible, efficient policy provides universal subsidies to skill development when the fraction of the disadvantaged group at the skill development margin is larger than their share at the slot assignment margin.